An ultra‐performance liquid chromatography–quadrupole time‐of‐flight tandem mass spectrometry method based on a four‐step analysis strategy to investigate metabolites of Qi‐Yu‐San‐Long decoction in rat plasma. (9th November 2022) - Zhao, Yue; Chen, Yang; Li, Ruijuan; Zheng, Ting; Huang, Mengwen; Gao, Yating; Li, Zegeng; Wu, Huan
Abstract : Metabolism is undoubtedly significantly correlated with the efficacy and safety of traditional Chinese medicine. In clinic, Qi‐Yu‐San‐Long decoction (QYSLD) has achieved good results in the treatment of non‐small‐cell lung cancer (NSCLC). Nevertheless, a detailed understanding of the compounds (prototypes and metabolites) of QYSLD and its dynamic metabolic profile in plasma has not been revealed. Methods: In this study, a rapid and sensitive method based on ultra‐performance liquid chromatography–quadrupole time‐of‐flight tandem mass spectrometry (UPLC–QTOF/MS E ), combined with a four‐step analysis strategy, was established to investigate QYSLD metabolic profile in rat plasma. Results: In all, 101 xenobiotics (41 prototypes and 60 QYSLD‐related metabolites) were identified in rat plasma. The research uncovered metabolic profiles of alkaloids, saponins, flavonoids, iridoids, anthraquinones, and phenylpropanoids of QYSLD in rat plasma. The dynamic changes in these xenobiotics were also observed at different time intervals. At 0.5 h after oral administration, only 15 prototypes and 11 metabolites were detected. Within 24 h, 4 prototypes and 20 metabolites can still be detected. Four prototypes and 10 metabolites had the phenomenon of emergence–disappearance–reappearance in vivo . Conclusion: In rat plasma, 101 xenobiotics of QYSLD were identified and their dynamic metabolic profiles were systematically delineated, which laid a material basis for further research of the pharmacodynamic substances of QYSLD inhibiting NSCLC.